1982
DOI: 10.1093/cvr/16.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smooth muscle activity on the static and dynamic elastic properties of the rabbit carotid artery

Abstract: The variation of radius with pressure was measured in vitro in the carotid artery of ten rabbits. Experiments were performed without prior conditioning of the vessel, over an inflation-deflation cycle at pressures in the range 0 to 24 kPa during treatment with, and in the absence of noradrenaline (referred to as active and passive conditions). The effect of a step change in pressure (2.7 kPa) on the radius of the vessel was investigated on a further three specimens. Under passive conditions, the variation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…Unstable resistance vessel diameters have been observed in some studies, with more than one possible radius at a given pressure and hysteretic behavior during loading and unloading [7] , [18] , [21] , [34] , [38] , [39] . In the present model, the possibility of such behavior can be assessed with reference to the results shown in Figure 2 (middle column).…”
Section: Discussionmentioning
confidence: 99%
“…Unstable resistance vessel diameters have been observed in some studies, with more than one possible radius at a given pressure and hysteretic behavior during loading and unloading [7] , [18] , [21] , [34] , [38] , [39] . In the present model, the possibility of such behavior can be assessed with reference to the results shown in Figure 2 (middle column).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that such measurements performed during the application of a single fixed pressure can be used to delineate regional urethra contractile responses in relation to axial changes in muscle composition and content (19). In principal, we now demonstrate that the experimental methodology utilized herein, which has traditionally been employed to characterize vascular tissue responses (12,14,17), may also be applied for the investigation of urethra functional properties within a physiological pressure range. The results obtained utilizing this methodology indicate that the female rat intrinsic urethral smooth muscle, compared with striated muscle, is capable of imparting a greater influence on the long-term functional responses of the urethra; the smooth muscle generated higher levels of maximum circumferential stress and also sustained higher levels of stress over a broader range of applied opposing pressures.…”
Section: Discussionmentioning
confidence: 78%
“…P-D responses became repeatable generally by the sixth to eighth inflation-deflation cycle, as observed through examination of resulting hysteresis loops. Note that preconditioning was not performed before the collection of active state data and is commonly avoided in studies of active mechanics due to concerns of compromising contractile function with repetitive stretching (12,14,17).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is possible that some mechanical/physical factors may have interacted with functional elements to enhance arterial compliance, as beat-by-beat arterial distension is significantly greater in central vs. peripheral arteries. In this context, the lower number of vascular smooth muscle cells and their differential geometry in central vs. peripheral arteries allows only a mild reduction in lumen diameter even when maximally stimulated by the sympathetic nervous system [24]. In the central elastic arteries, the vasoconstrictor tone exerted by its smooth muscle cells appear to modulate arterial compliance through redistribution of tensile force between elastin and collagen [25].…”
Section: Discussionmentioning
confidence: 99%